Pelatihan Perakitan Dan Instalasi Komputer Pada SMP Ar Rahman - Husin Sariangsah; Firman Syahputra (Lembaga Pengembangan Kinerja Dosen, 2024)
The Tridharma of Higher Education contains three important points, namely education, research and community service. Community service on this occasion was carried out with partners from Ar Rahman Junior School. Current technological developments, especially computer technology, are very advanced. In Indonesia, many computer products are marketed with various types, prices and specifications. The computer hardware component manufacturing industry competes with each other to satisfy consumers and customers. Computer assembly and installation are important processes in the development and maintenance of efficient and reliable computer systems. In-depth knowledge of assembly and installation procedures is key to ensuring optimal performance as well as system safety. For this reason, there is a need for computer assembly and installation training for students at Ar Rahman junior School who have the knowledge and skills in assembling and installing their own computers properly and are able to implement it at school.